2016
DOI: 10.18488/journal.107/2016.4.4/107.4.127.133
|View full text |Cite
|
Sign up to set email alerts
|

A Supply-Lock Competitive Market for Investable Products

Abstract: We propose a new market structure, a supply-lock competition (SLC), for analyzing transactions of investable goods. This study explains and analyzes how the SLC is applicable for transactions of stock, art, real estate, currency, and scarce goods. We suggest that the formation and fluctuation of the market price for these investable assets are not only related to their intrinsic values or investors' behavior, but are also derived from supply restriction. A mechanism of the SLC market structure benefits market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…These systems enable users to realize the status of the performance in the supply chain such as strengths, weaknesses, and the levels of current performance in order to allow companies to make informed decisions towards the opportunities and threats. Organizations are able to take appropriate actions at the right time (Christopher, 2011) to effectively improve their performance (Nasiri et al, 2010;Solomon et al, 2014;Castorena et al, 2014;Dim & Ezeabasili, 2015;Angbre, 2016;Wang & Lu, 2016;Purnama, 2014;Nazal, 2017;Tanoos, 2017;Maldonado-Guzman, et al, 2018;Taqi et al, 2018).…”
Section: Supply Chain Operational Performancementioning
confidence: 99%
“…Generally, supply chain digitalization comes under electronic supply chain (e-supply chain) (Poirier & Bauer, 2000). Digitalization facilitates supply chain activities of business (Castorena et al, 2014;Dim & Ezeabasili, 2015;Wang & Lu, 2016;Vendrell-Herrero et al, 2017).…”
Section: Introductionmentioning
confidence: 99%